Ergonomics in dentistry: experiences of the practice by dental students - Garcia, P. P.N.S. [UNESP]; Gottardello, A. C.A. [UNESP]; Wajngarten, D. [UNESP]; Presoto, C. D. [UNESP]; Campos, J. A.D.B. [UNESP] (Wiley, 2017)
Objective: The aim of this study was to qualitatively evaluate the experiences of students enrolled in the last year of dentistry school with ergonomic practice. Methods: This is a qualitative, observational and cross-sectional study, with a non-probabilistic sample design. The sample comprised students enrolled in the last year of dentistry in Araraquara–UNESP (n = 29). The data were collected by means of open semi-structured and individual interviews, captured by a digital voice recorder. The students were interviewed in their own university at a time that was previously scheduled, and care was taken to provide a private and welcoming environment to carry out the interviews. A script containing questions related to practices in ergonomics was prepared at the university. Data analysis was carried out using the qualitative–quantitative Collective Subject Discourse technique with the aid of Qualiquantisoft® software program. Results: It was found that more than half of the students (58.6%) believe that adopting an ergonomic posture is important to prevent future problems, pain and occupational diseases, and 62.1% of the students confirm having difficulties in adopting ergonomic postures due to the types of treatment required and the regions of the mouth being treated. The main reasons stated for the fact that their colleagues do not adopt ergonomic postures are lack of attention, practice and forgetfulness (44.8%) and difficulty in visualising the operatory field or the procedure performed (27.6%). Conclusion: It is possible to conclude that the students interviewed know ergonomic principles and their importance in occupational health. However, they found it difficult to put these principles into practice.
Keywords: interview; occupational diseases; students